2022
DOI: 10.34067/kid.0005882022
|View full text |Cite
|
Sign up to set email alerts
|

The Cleveland Clinic Kidney Biopsy Epidemiological Project

Abstract: Background: The kidney biopsy is the gold standard for the diagnosis of glomerular diseases. Large-scale, epidemiological studies describing the prevalence of kidney diseases are lacking especially in the US. We aimed to determine the spectrum of biopsy proven kidney disease across the Cleveland Clinic enterprise. Methods: We identified all patients with a native kidney biopsy performed/reviewed at the Cleveland Clinic from January 2015 to September 2021. Retrospective chart review was performed to obtain clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…This registry revealed variations in the age and gender distribution among different practice patterns. The average age of patients in this study was comparable to previous reports from Thailand but lower compared with other countries 6,8,9,11–13 . Older age has been associated with different final diagnoses in various registries, with several studies indicating a correlation between glomerular injury patterns and patient age 6,8,9,14 .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This registry revealed variations in the age and gender distribution among different practice patterns. The average age of patients in this study was comparable to previous reports from Thailand but lower compared with other countries 6,8,9,11–13 . Older age has been associated with different final diagnoses in various registries, with several studies indicating a correlation between glomerular injury patterns and patient age 6,8,9,14 .…”
Section: Discussionsupporting
confidence: 79%
“…Older age has been associated with different final diagnoses in various registries, with several studies indicating a correlation between glomerular injury patterns and patient age 6,8,9,14 . For instance, a large epidemiological report from the Cleveland Clinic involving 4123 patients demonstrated that individuals over 70 years of age were more likely to have FSGS, while those below 45 years had a higher likelihood of IgAN 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations